Palaeoenvironmental study of benthic foraminifera from the late Pleistocene Puente de Pascua Formation type locality, Buenos Aires province, Argentina - Petriella, Julieta (2023)
This paper examines the palaeoenvironmental conditions of a Late Pleistocene marine unit assigned to the Puente de Pascua Formation (MIS 5e), Buenos Aires, Argentina. For this study, a micropalaeontological (Phylum Foraminifera) and lithological analysis was conducted, based on a PPas-section extracted in the Puente de Pascua site, located 32 km inland from the coastline of Bahía Samborombón (35°55′37” S; 57°43 ′7.6” W). The base of this section comprises finely stratified with brown clays, followed by a layer of dark brown sandy sediments with layers of shells, interspersed with light brown to yellowish deposits. Hyaline foraminifera of relative well preservation and small size prevail. The assemblage was represented mainly by Buccella peruviana and Ammonia parkinsoniana accompanied by other species such as Elphidium galvestonense, Ammonia tepida, Cribroelphidium poeyanum and Bolivina spp. in minor proportion. From this integrated study, palaeoenvironmental changes were established in Puente de Pascua Fm. (>66.5 kyrs). Results reflect transition from a tidal flat depositional environment towards a littoral estuarine environment.